Finite volume approximation of stiff problems on two-dimensional curvilinear domain. Issue 10 (2nd October 2016) - Faure, Sylvain; Tekitek, Mohamed Mahdi; Temam, Roger
Abstract : The aim of this article is to apply a novel finite volume method to approximate a stiff problem for a two-dimensional curvilinear domain. The stiffness is caused by the existence of a small parameter in the equation which introduces a boundary layer along parts of the curvilinear boundary. Incorporating in the finite volume space the boundary layer correctors, the boundary layer singularities are absorbed. Hence, we propose a second order scheme for curvilinear domains using uniform meshes thus avoiding the costly refinement of mesh in the boundary layers.